2014
DOI: 10.1128/mcb.00333-14
|View full text |Cite
|
Sign up to set email alerts
|

HuR Regulates Alternative Splicing of the TRA2β Gene in Human Colon Cancer Cells under Oxidative Stress

Abstract: bHu antigen R (HuR) regulates stress responses through stabilizing and/or facilitating the translation of target mRNAs. The human TRA2␤ gene encodes splicing factor transformer 2␤ (Tra2␤) and generates 5 mRNA isoforms (TRA2␤1 to -5) through alternative splicing. Exposure of HCT116 colon cancer cells to sodium arsenite stimulated checkpoint kinase 2 (Chk2)-and mitogen-activated protein kinase p38 (p38 MAPK )-mediated phosphorylation of HuR at positions S88 and T118. This induced an association between HuR and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 66 publications
2
64
0
Order By: Relevance
“…Some RBPs can also regulate multiple posttranscriptional processes. For example, NF90 can regulate both mRNA translation and turnover, whereas HuR and TIA1 can affect mRNA translation, turnover, and pre‐mRNA splicing (Akaike et al, ; Del Gatto‐Konczak et al, ; Hamada et al, ; Masuda et al, ; Piecyk et al, ; Shim, Lim, Yates, & Karin, ; Y. H. Xu, Busald, & Grabowski, ; Y. H. Xu & Grabowski, ; Y. H. Xu, Leonova, & Grabowski, ).…”
Section: Major Functions Of Rbps In Gene Expression Regulationmentioning
confidence: 99%
“…Some RBPs can also regulate multiple posttranscriptional processes. For example, NF90 can regulate both mRNA translation and turnover, whereas HuR and TIA1 can affect mRNA translation, turnover, and pre‐mRNA splicing (Akaike et al, ; Del Gatto‐Konczak et al, ; Hamada et al, ; Masuda et al, ; Piecyk et al, ; Shim, Lim, Yates, & Karin, ; Y. H. Xu, Busald, & Grabowski, ; Y. H. Xu & Grabowski, ; Y. H. Xu, Leonova, & Grabowski, ).…”
Section: Major Functions Of Rbps In Gene Expression Regulationmentioning
confidence: 99%
“…We recently have revealed that RNA binding protein could promote fibrogenic response through stabilizing TGFb in cardiac fibroblasts [10]. In addition, HuR was found to be activated under multiple stress conditions, such as oxidative stress [11], UV light exposure [12], inflammation [13] and hypoxia [14]. Taken together, it is reasonable to hypothesize that angiotensin II might activate HuR and then promotes fibrosis via TGFb signal pathway.…”
Section: Introductionmentioning
confidence: 99%
“…25 HuR functions in nucleus and mediates stress responses by stabilizing and/or promoting the expression of target mRNAs, while SFRS10 includes AU-rich elements in exon 2, in which exists a HuR-binding motif. 16 HuR may participate in splicing regulation of SFRS10 pre-mRNA after exposure to oxidative stress ( Figure 1). Akaike et al have demonstrated that both Chk2-and mitogen-activated protein kinase p38 (p38MAPK)-dependent phosphorylation of HuR induce SFRS10 exon 2 retention and interact with the 39-nucleotide proximal domain of exon 2, reducing the expression of SFRS10 in HCT116 cells exposed to sodium arsenite.…”
mentioning
confidence: 99%
“…Akaike et al have demonstrated that both Chk2-and mitogen-activated protein kinase p38 (p38MAPK)-dependent phosphorylation of HuR induce SFRS10 exon 2 retention and interact with the 39-nucleotide proximal domain of exon 2, reducing the expression of SFRS10 in HCT116 cells exposed to sodium arsenite. 16 Chk2-and p38MAPK-mediated phosphorylation of nuclear HuR at residue serine 88 and/or tyrosine 118 urges the association between HuR and exon 2a of SFRS10 pre-mRNA in colon cancer cells exposure to oxidants, and promotes the formation of TRA2b 4 transcript that does not translate. 16 Oxidative stress may promote the retention of SFRS10 exon 2 to reduce SFRS10 expression via phosphorylating HuR.…”
mentioning
confidence: 99%
See 1 more Smart Citation